The impact of gymnastics experience on the acquisition of new gymnastics skills - Delaš Kalinski, S.; Penjak, A.; Piteša, I. (International Scientific Congress Slovenian Gymnastics Federation, 2018)
The transfer between motor skills occurs when previously adopted motor skill affect learning and levels of another (new) motor skill. The aim of this study was to determine the influence of previously acquired theoretical and practical experiences on the level of skills acquisition from the Theory and Methodics of Artistic gymnastics 1 course programme. The sample consisted of 67 (39 students (58.21% and 28 students (41.79%), the average age 21.34 ± 1.32 years) students from the Faculty of Kinesiology, University of Split, Croatia. The results have shown: 1) both sexes have very low practical and theoretical foreknowledge about artistic gymnastics; 2) no significant differences were identified in the level of acquisition of skills from any gymnastics apparatus between male students with some foreknowledge and those without foreknowledge of artistic gymnastics; 3) there are significant differences between female students with foreknowledge and those without foreknowledge of artistic gymnastics in the level of vault skills (no significant differences were found on other apparatus). The obtained results confirm the Specificity of motor abilities hypothesis (SMA hypothesis) but also emphasize that an adequate teaching programme neutralizes the influence of foreknowledge on learning a new motor skill.